Some aspects of judicial constitutional control in foreign countries - Yerzhanova, F.A. (Вестник Карагандинского университета, 2016)
The article is devoted to the value and role of the institution of judicial constitutional control in foreign coun- tries. It presents issues of specificity of judicial constitutional review, differences between the institutional forms of constitutional control, operating in various foreign countries. Considerable attention is paid to the forms and varieties of the Institute of constitutional review, to the problems of the preliminary and subsequent constitutional control in countries with different legal systems. This article discusses the conceptual issues about the role and place of judicial constitutional review in the system of state authority. On the basis of the analysis of constitutional and legal legislation of foreign countries the system of objects of judicial constitu- tional control is given, furthermore, the role of constitutional review as an important and necessary element in the overall constitutional system of power is displayed.
Keywords: Constitutional legality; the system of state authority; constitutional review; judicial constitutional control